2016
DOI: 10.1007/s11367-016-1212-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative life cycle assessment and life cycle costing of lodging in the Himalaya

Abstract: The main aim of the study is to assess the environmental and economic impacts of the lodging sector located in the Himalayan region of Nepal, from a life cycle perspective. The assessment should support decision making in technology and material selection for minimal environmental and economic burden in future construction projects.\ud The study consists of the life cycle assessment and life cycle costing of lodging in three building types: traditional, semi-modern and modern. The life cycle stages under analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 30 publications
3
16
0
Order By: Relevance
“…2.1. Study design, study area and typical building types Bhochhibhoya et al (2016) compared the life cycle environmental impacts and costs of three buildings in Sagarmatha National Park and Buffer Zone (SNPBZ): a traditional building, a semimodern one, and a modern one. However, the comparison was limited to three buildings and did not allow drawing generalizable conclusions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2.1. Study design, study area and typical building types Bhochhibhoya et al (2016) compared the life cycle environmental impacts and costs of three buildings in Sagarmatha National Park and Buffer Zone (SNPBZ): a traditional building, a semimodern one, and a modern one. However, the comparison was limited to three buildings and did not allow drawing generalizable conclusions.…”
Section: Methodsmentioning
confidence: 99%
“…To give a more comprehensive picture on the environmental and economic aspects of the life cycle of Himalayan buildings, this study considers a larger sample of lodges of a different type located in all three Village Development Committees (VDC) of the Park. The same LCA modeling as in Bhochhibhoya et al, (2016Bhochhibhoya et al, ( , 2017 was applied to assess the environmental footprint and costs of all the buildings. In addition, new parameters such as heat loss rate, number of guests, and area of the lodges were measured that are then analyzed and documented in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on their research, these authors also point out that the use of wood in construction contributes to a significant reduction in CO 2 production and a reduction in the use of fossil fuels needed to produce building materials and structural elements. Bhochhibhoya et al [71] conducted a study similar to ours, the environmental and economic characteristics of the comparative variants of building construction systems. The above-mentioned authors have found that the use of local building materials whose production is not energy-intensive is far more environmentally beneficial than materials whose production pollutes environmentally and draws a lot of resources.…”
Section: Discussionmentioning
confidence: 81%
“…The application of consequential LCA, which is relatively new to emerging economies, has been attempted in analyzing policy decisions showing the coming-of-age of LCA in these countries (Prapaspongsa and Gheewala 2017;Prateep Na Talang et al 2017). The combination of life cycle -based environmental and economic tools is a first step towards life cycle sustainability assessment (LCSA); studies have been done using tools such as LCA, LCC, and economically extended material flow analysis (Bhochhibhoya et al 2017;Khonpikul et al 2017). Finally, a full LCSA has also been attempted considering LCA, LCC, and SLCA (van Kempen et al 2017).…”
mentioning
confidence: 99%